Brachial Plexus Anatomy of Sprague Dawley Rat Compared to Human - Alison N. Jacobs; Luke J. Bolstad; Natalie Martinson; Ethan Mickelson; Matthew R. Ceelen; Owen R. Lefebvre; Roy Ram Klein; Daniel J. Hellenbrand; Amgad S. Hanna (Journal of Brachial Plexus and Peripheral Nerve Injury)
Brachial plexus injury (BPI) occurs when the brachial plexus (BP) is compressed, stretched, or avulsed. A mild BPI results in acute arm pain, tingling, or numbness, while more severe injuries can lead to permanent muscle weakness or loss of function of the extremity if left untreated. Many BPI treatments developed in small animal models fail to translate effectively to human clinical trials. Furthermore, there is a lack of comparative studies exploring the anatomical differences between BPs in different species. The objective of this study is to compare the BP anatomy between humans and Sprague–Dawley (SD) rats to determine if the SD rat is a suitable model for studying BPI mechanisms and treatments. Four human BPs were compared to five SD rat BPs. Gross anatomical analysis revealed mild similarities in the branching patterns of SD rat and human BP. Histological results indicated that SD rats had significantly smaller musculocutaneous (p = 0.0095), median (p < 0.0001), and ulnar (p < 0.0001) nerves compared to humans. Additionally, SD rats had significantly fewer axons than humans in the musculocutaneous (p = 0.0190), median (p < 0.0001), and ulnar nerves (p < 0.0001). Due to the anatomical and histological differences between the two species, therapeutic interventions for BPIs developed in rats should be further tested in a larger animal model, such as the Wisconsin Miniature Swine, before progressing to human clinical trials.